Sams teach yourself E-commerce programming with asp in 21 days - Walther, Stephen; Banick, Steve; Levine, Jonathan ([S.l.] : Sams Publishing, 2000)
The friendly, tutorial style of Sams Teach Yourself E-Commerce Programming with ASP in 21 Days empowers you to create your own online stores quickly and easily. Using online-proven methods, Stephen Walther, an expert e-commerce developer, provides you with an understanding of online commerce applications, then guides you through the use of VBScript and ASP's built-in objects, enabling you to create your own dynamic, database-driven e-commerce solutions. This book does not stop at just creating the online store. The author teaches you to create order tracking systems, manage advertising, create store reports, personalize the shopping experience and much more.